Mortality response of new chemistry insecticides against Thrips orientalis (Thysanoptera: Thripidae) on jasmine under field conditions (Zoo Botanica, 2025)
Thrips orientalis is an important sap-sucking insect pest affecting various crops, including Jasmine. Chemical control is one of the most commonly employed methods for its management. The efficacy of several insecticides at their recommended field dosage on Jasmine plants against T. orientalis was evaluated. After 240 h, mortality was the highest with fipronil (96%) followed by emamectin benzoate (94%) for the first spray. Following second spray application, mortality with fipronil was 96.8% followed by emamectin benzoate as 94.9% with similar trend as for the first spray application. Out of nine insecticides tested, pyriproxyfen was least effective with 71.1% and 71.9% 240 h after first and second application, respectively. Means of both applications showed fipronil with the highest mortality rate (96.5%) followed by emamectin benzoate (94.5%) which are recommended for effective field management of T. orientalis on Jasmine plants.
Keywords: Thrips orientalis; field application; insecticides; mortality